A Note on "A Four-Flagged Lemma" - Vind, Karl (Review of Economic Studies, 1974)
Journal Article A Note on “A Four-Flagged Lemma” Get access Karl Vind Karl Vind University of Copenhagen Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 4, October 1974, Page 571, https://doi.org/10.2307/2296707 Published: 01 October 1974